2017
DOI: 10.1016/j.bjid.2017.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Human Bocavirus type 4 in a child asymptomatic for respiratory tract infection and acute gastroenteritis – Goiânia, Goiás, Brazil

Abstract: Human Bocavirus (HBoV) has been identified from feces and respiratory samples from cases of both acute gastroenteritis and respiratory illness as well as in asymptomatic individuals. The aim of this study was to detect and characterize HBoV from fecal samples collected from hospitalized children aged less than five years old with no symptoms of respiratory tract infection (RTI) or acute gastroenteritis (AGE). The study involved 119 children and one fecal sample was collected from each participant between 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…The role of Human Bocavirus as the single causative agent for respiratory tract infections remains unclear as detection in children is frequently in combination with other viruses or bacteria in a co-infection state [57,58]. Furthermore, Human Bocavirus can remain in transient state after recovery and can be isolated from healthy individuals [59]. In the last two decades, three novel coronaviruses have emerged in the humans that can cause ARTI with symptoms of fever, sore throat, cough, chills, and muscle pain leading to more severe acute respiratory distress syndrome.…”
Section: Advantages Disadvantages and Challenges In The Interpretation Of Resultsmentioning
confidence: 99%
“…The role of Human Bocavirus as the single causative agent for respiratory tract infections remains unclear as detection in children is frequently in combination with other viruses or bacteria in a co-infection state [57,58]. Furthermore, Human Bocavirus can remain in transient state after recovery and can be isolated from healthy individuals [59]. In the last two decades, three novel coronaviruses have emerged in the humans that can cause ARTI with symptoms of fever, sore throat, cough, chills, and muscle pain leading to more severe acute respiratory distress syndrome.…”
Section: Advantages Disadvantages and Challenges In The Interpretation Of Resultsmentioning
confidence: 99%
“…7,9,22 In Brazil, HBoV-4 was previously identified only once in a fecal sample from a hospitalized child with a soft tissue tumor in the submandibular region in 2015, supporting the low prevalence of HBoV-4 circulating in the country. 50 Worldwide, HBoV coinfection with other enteric viruses is reported. 11,30,32,33 Our findings indicate a higher proportion of HBoV monoinfection (65.2%) compared to coinfection (34.9%), aligning with data from Egypt and Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The final dataset included data on children from 20 countries (Russia, United States, India, China, Brazil, Albania, Korea, Japan, Sudan, Gabon, Latvia, Iraq, Iran, South Africa, Bangladesh, Australia, Finland, United Kingdom, Thailand, and Egypt). Of the sectional in study design (20,. Amidst the cross-sectional studies, 23 were caseonly, and the remaining 2 presented data for healthy individuals.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most recently, Neveen et al concluded that HBoV could be the significant etiologic agent of gastroenteritis due to the presence of HBoV in some children suffering from diarrheal disease without any association of any other etiological agents (19). However, a controversial issue that arises in this domain is the actual pathogen role of HBoV in gastrointestinal symptoms due to the growing appears of HBoV detection in asymptomatic patients (20,21).…”
Section: Introductionmentioning
confidence: 99%